Penerapan Diaphragmatic Breathing Exercise terhadap Pernapasan SPO2 Pada Pasien Penyakit Paru Obstruktif Kronik (PPOK) dengan Masalah Keperawatan Pola Nafas Tidak Efektif di Rumah Sakit Bintang Amin - Juana, Rika; Andoko, Andoko; Keswara, Umi Romayati (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT  The prevalence of Chronic Obstructive Pulmonary Disease (COPD) in Southeast Asia reaches 6.3% with sufferers aged over 30 years. The number of Chronic Obstructive Pulmonary Disease (COPD) in Indonesia reaches 9.2 million people or around 3.7%. While the prevalence of Chronic Obstructive Pulmonary Disease (COPD) in Lampung reaches 3.4%. COPD sufferers usually complain of symptoms of shortness of breath, coughing, and fatigue in daily activities. Therefore, the need for proper management is very necessary to reduce dyspnea in COPD patients, which can be done with breathing exercises, one of which is doing breathing exercises by applying Diaphragmatic Breathing Exercise. To provide geriatric nursing care for COPD clients with ineffective breathing pattern nursing problems by applying diaphragmatic breathing exercise. In writing this final project report, a descriptive research design with a case study design was used. The subjects used were 3 people who experienced nursing problems of ineffective breathing patterns. The application of Diaphragmatic Breathing Exercise for the intervention group was 2 times a day for 5-10 minutes per day for 3 days. The application of diaphragmatic breathing exercise therapy can reduce the frequency of breathing in COPD patients. Nursing management of ineffective breathing patterns with the application of diaphragmatic breathing exercise therapy nursing actions that the author did for 3 days in COPD patients where the problem of ineffective breathing patterns in clients is more effective in Mr. M and Mr. A compared to Mr. S. This proves that there is an effect of the application of diaphragmatic breathing exercise therapy to reduce the frequency of breathing in COPD patients compared to not doing diaphragmatic breathing exercise therapy. Keywords: COPD, Diaphragmatic Breathing Exercise, Ineffective Breathing Pattern. ABSTRAK Prevalensi Penyakit Paru Obstruktif Kronik (PPOK) di Asia Tenggara mencapai 6,3% dengan usia penderita lebih dari 30 tahun. Angka Penyakit Paru Obstruktif Kronik (PPOK) di Indonesia menjangkau 9,2 juta orang atau kisaran 3,7%. Sedangkan prevalensi Penyakit Paru Obstruktif Kronik (PPOK) di Lampung mencapai 3,4%. Penderita PPOK biasanya mengeluhkan gejala sesak napas, batuk, serta kelelahan dalam beraktivitas sehari-hari. Diperlukannya tatalaksana pada pasien PPOK untuk menurunkan dyspneau yaitu dengan penerapan latihan napas diafragma. Metodologi penelitian ini menggunakan desain penelitian deskriptif. intervensi ini dilakukan 2 kali selama 5-10 menit selama 3 hari. Penerapan terapi latihan pernapasan diafragma dapat mengurangi frekuensi pernapasan pada pasien PPOK.  Pengelolaan pembasmian pola pernapasan tidak efektif dengan penerapan tindakan pemeliharaan terapi pernafasan diafragma yang penulis lakukan selama 3 hari pada pasien PPOK dimana masalah pola pernafasan tidak efektif pada klien lebih efektif pada Tn. M dan Tn. A dibandingkan dengan Tn. Hal tersebut membuktikan terdapat pengaruh penerapan terapi latihan pernapasan diafragma untuk mengurangi frekuensi pernapasan pada pasien PPOK dibandingkan tidak dilakukannya tindakan terapi latihan pernapasan diafragma. Kata Kunci: PPOK, Latihan Pernapasan Diafragma, Pola Nafas Tidak Efektif